Aquamarine - Hoffman, Alice (New York : Scholastic Press, 2001)
A love-struck mermaid named Aquamarine supplies adventure and insights to two twelve-year-old girls, life-long friends who are spending their last summer together before one of them moves away.
New York Times.
Bulletin (Center for Children's books).
Voice of Youth Advocates (V.O.Y.A.).
5.9
5-8
Keywords: Mermaids -- Fiction; Friendship -- Fiction; Summer -- Fiction; Beaches -- Fiction; Moving, Household -- Fiction; Mermaids and mermen -- Fiction; Friendship -- Fiction; Summer -- Fiction; Beaches -- Fiction; Moving -- Fiction; Mermaids -- Fiction; Friendship -- Fiction; Summer -- Fiction; Beaches -- Fiction; Moving, Household -- Fiction